Perancangan Logo dalam Dunia Desain - Monica Monica; Laura Christina Luzar (Bina Nusantara University, 2013)
Since the beginning logo recognized, it already has experienced development in terms of reasoning aspect. At the beginning logo meant words, mind, symbol, image, and semiotic, then changes into flag, signature, and symbol, which indirectly can provide the identity, information, and persuasion that eventually functions as media for marketing. In the design world, it always appears questions about the importance of a logo should be designed. Here is the thing discussed through the description of the function of a logo and the process of designing a logo. Because not all the redesign of an existing logo will bring better imaging results although the main goal of designing a logo is for positive things.